Β‐Heptasubstituted Porphyrins: Synthesis, Structural, Spectral, and Electrochemical Properties. Issue 28 (23rd July 2018) - Grover, Nitika; Kumar, Ravi; Chaudhri, Nivedita; Butcher, Ray; Sankar, Muniappan
Abstract : A new series of β‐heptasubstituted porphyrins MTPP(NO2 )(Me)6 (M = 2H, Co II, Ni II, Cu II, and Zn II ) was synthesized and characterized by various spectroscopic techniques. The single‐crystal X‐ray structure analysis of CoTPP(NO2 )(Me)6 revealed the significant saddle distortion of the macrocyclic core from the porphyrin mean plane (Δ C β = 0.928 Å). These porphyrins exhibit significant redshifted electronic spectral features (Δ λ max = 40–62 nm) as compared with MTPP due to the combined effect of the nonplanar conformation of the macrocyclic core and mixed β‐substituents. H2 TPP(NO2 )(Me)6 has shown a high dipole moment (7.12 D) as compared with H2 TPP (0.052 D) due to cross‐polarized push–pull substituents. The redox tunability was achieved by appending the electron‐donating methyl and electron‐withdrawing NO2 group at the β‐positions of the porphyrin skeleton. Abstract : A series of β‐heptasubstituted porphyrins [MTPP(NO2 )(Me)6 ] was synthesized and the single‐crystal XRD of CoTPP(NO2 )(Me)6 revealed the significant saddle distortion of the macrocyclic core from the mean plane. MTPP(NO2 )(Me)6 exhibited redshifted electronic spectral features and a reduced HOMO–LUMO gap due to the combined effect of push–pull β‐susbtituents and the nonplanarity of the porphyrin.